Expediente e Nominata - REVER, Redação (REVER: Revista de Estudos da Religião, 2020)
Avaliadores desta edição: Alex Villas Boas (UCP, Portugal); Alexandre B. Pereira (UNIFESP, São Paulo-SP); Alexandre Carvalho Pitta (UFBA, Salvador-BA); Bruno N. Huyer (IPHAN, São Paulo-SP); Camila C. Arêas (UNIV-REUNIÓN, França); Carine Lavrador de Farias (autônoma); Carlos A. Cavalcanti (UFPB, João Pessoa-PB); Catarina Silva Nunes (UCP, Portugal); Cátia Ferreira (UCP, Portugal); Cátia Tuna (UCP, Portugal); Clara Falksman (autônoma); Cristiano Camilo Lopes (UPM, São Paulo-SP); Dalva A. Monteiro (UEFS, Feira de Santana-BA); Débora D. Dell’Aglio (UNILASALLE, Canoas-RS); Deivison M. C. de Campos (ULBRA, Canoas-RS); Donizete Rodrigues (UBI, Portugal); Elaine Costa Honorato (UFAC, Rio Branco-AC); Elsa Margarida da Silva Rodrigues (UC, Portugal); Fábio L. Stern (PUC-SP, São Paulo-SP); Inês Espada Vieira (UCP, Portugal); Isabel Patim (UFP, Portugal); João Marques Eleutério (UCP, Portugal); Joêzer de Souza Mendonça (autônomo); Jorge Miguel Acosta Soares (autônomo); José Pedro Lopes Angélico (UCP, Portugal); José Rui Teixeira (UCP, Portugal); Krzysztof Dworak (UNEB, Salvador-BA); Leonor Losa (UNL, Portugal); Luis Miguel Figueiredo Rodrigues (autônomo); Luísa Maria Varela Almendra (UCP, Portugal); Luiz Carlos Luz Marques (UNICAP, Recife-PE); Márcia L. Pinheiro (UENF, Campos dos Goytacazes-RJ); Marcio C. A. Lopes (UMESP, São Bernardo do Campo-SP); Marco A. Nunes da Silva (UFRB, Cachoeira-BA); Marcus Vinicius Reis (UNIFESSPA, Marabá-PA); Maria do Rosário L. Lupi Bello (UCP, Portugal).; Mylene Mizrahi (PUCRio, Rio de Janeiro-RJ); Olívia Bandeira (autônoma); Peter Stiwell (USJ, China); Rodrigo C. Caldeira (PUC Minas, Belo Horizonte-MG). Rodrigo Ferreira Toniol (UFRJ, Rio de Janeiro,RJ); Rodrigo O. Santos. (ACREPA, Belém-PA); Rui Manuel Brás (UCP, Portugal); Rui Miguel Fernandes (UCP, Portugal); Sergio S. D. Vasconcelos (UNICAP, Recife-PE); Yara Schreiber Dines (UNESP, Araraquara-SP)